Design and Implementation of a DC/Dc Boost Converter with PID Control for Regenerative Braking Application - Alcántara Vásquez, Jorge Cristhofer (2024)
This article presents the design and implementation of a 12 V to 40,99 V DC/DC boost converter using PID control, with the aim of providing an efficient solution for harnessing recovered energy in a regenerative braking system. In the first stage, the uncontrolled circuit was designed using Simulink and PSIM software. Subsequently, a prototype of the controlled circuit was implemented using PID control to correct the output signal. Once the prototype’s functionality was validated in the Proteus simulator, the physical implementation was carried out. This phase included the design of the tracks in Eagle software, the modeling of the board in Autodesk Fusion, and the manual fabrication of the circuit. The use of PID control allowed for an average output voltage of 40,99 V, a similar RMS value, and a peak-to-peak ripple voltage of 2,40 V. Although the maximum estimated in the simulations was not reached, the results confirm the proper operation of the converter. Additionally, potential improvements were identified to optimize the circuit’s performance, such as adjustments in capacitance or inductance, in order to reduce current and voltage spikes.